2018
DOI: 10.22610/jebs.v10i2.2218
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Stressors and Work-Family Satisfaction: Effect of Sense of Coherence at a Metropolitan Municipality

Abstract: This article contributes to emergent research by examining the linkage between work-family stressors and their effect on work-family satisfaction (WFS) at a metropolitan municipality in South Africa. Extant literature on stress has either not adequately examined the linkage between domain specific stressors and domain specific satisfaction or have suggested models with direct connections. The present study suggests a mediating model and assesses the mediation. Specifically, it claims that sense of coherence (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…They argue that, taking up more job responsibilities to meet up with the job demands is crucial to achieve the organisational set goals and meet the needs of the stakeholders. A similar study conducted by Huyghebaert et al (2016) This finding of this study is not surprising, as previous empirical studies have revealed that, workaholics are obsessed with work resulting in working for long hours either consciously or unconsciously (Abe et al, 2018;Gillet, Morin, Cougot & Gagné, 2017;Stoeber & Damian, 2016). In addition, Clark et al (2014) revealed that workaholics tend to work longer hours and often miss spending quality time with the family.…”
Section: Causes Of Workaholismsupporting
confidence: 78%
See 1 more Smart Citation
“…They argue that, taking up more job responsibilities to meet up with the job demands is crucial to achieve the organisational set goals and meet the needs of the stakeholders. A similar study conducted by Huyghebaert et al (2016) This finding of this study is not surprising, as previous empirical studies have revealed that, workaholics are obsessed with work resulting in working for long hours either consciously or unconsciously (Abe et al, 2018;Gillet, Morin, Cougot & Gagné, 2017;Stoeber & Damian, 2016). In addition, Clark et al (2014) revealed that workaholics tend to work longer hours and often miss spending quality time with the family.…”
Section: Causes Of Workaholismsupporting
confidence: 78%
“…Often, a workaholic does not necessarily have to work for long hours but chooses to do so at the expense of other life demands. A workaholic compulsive tendency to work for long hours result in the reduction of hours spent at home with the family (Abe, Abe, Fields & Ganiyu, 2018). Sometimes workaholics do not see themselves as such; they just buried themselves in work losing track of time, which becomes a regular occurrence in the process.…”
Section: Work-life Balance Strategies and The Concept Of Workaholismmentioning
confidence: 99%